MENGAJAR DAN GURU DALAM PERSPEKTIF AL-QURAN - Muhartini Muhartini; Munzir Hitami; Kadar Yusuf (Jurnal Literasiologi, 2023)
The educational process expects humans to carry out their obligations as caliphs on this earth well. Education is meant here is a teaching activity. Muslims make al-Qur'an as a guide for life. In a sense, all the problems he faces must be returned to the Qur'an. In this case, not only does al-Qur'an as reading material only, so that the instructions contained in the Qur'an will not be known, nor will the instructions of the Qur'an against education problems. There are four teaching concepts in the perspective of the Qur'an, namely 'allama, rabba, darrasa, and 'addaba. The principle of teaching in the perspective of the Qur'an is also inseparable from the principles of monotheism and divine, besides that there is the principle of compassion which gives birth to other teaching principles, namely sincerity, democracy, gentleness, and tolerance for students. In the context of Islamic education, teachers are all parties who try to improve others Islamically. Duties and Responsibilities of Teachers in the Perspective of the Qur'an, namely the teacher is the person in charge of continuing the duties of the prophets and apostles, the teacher is in charge of delivering students to achieve their life goals, the teacher is tasked with continuing the duties of the scholars as messengers of religion to others. the student, the student's problem solver wisely, enjoins the good, forbids the bad. The responsibilities of a teacher in the perspective of the Qur'an are as murabb?, Mu'allim, Mu'addib, Mudarris, and Mursyid. As a result of this writing, the author suggests to the readers to be able to reproduce more references and not focus only on the material that has been compiled, so that the knowledge we have is even wider.